Engineering a photosynthetic bacteria-incorporated hydrogel for infected wound healing. (1st March 2022) - Zhao, Erman; Liu, Huifang; Jia, Yaru; Xiao, Tingshan; Li, Jiaxin; Zhou, Guoqiang; Wang, June; Zhou, Xiaohan; Liang, Xing-Jie; Zhang, Jinchao; Li, Zhenhua
Abstract: Treating wounds with multidrug-resistant bacterial infections remains a huge and arduous challenge. In this work, we prepared a "live-drug"-encapsulated hydrogel dressing for the treatment of multidrug-resistant bacterial infections and full-thickness skin incision repair. Our live dressing was comprised of photosynthetic bacteria (PSB) and extracellular matrix (ECM) gel with photothermal, antibacterial and antioxidant properties, as well as good cytocompatibility and blood compatibility. More interestingly, live PSB could be regarded as not only photothermal agents but also as anti-inflammatory agents to promote wound healing owing to their antioxidant metabolites. In vitro and in vivo studies showed that the PSB hydrogel not only had a high killing rate against methicillin-resistant Staphylococcus aureus (MRSA) but it also accelerated collagen deposition and granulation tissue formation by promoting cell proliferation and migration, which significantly promoted skin tissue regeneration and wound healing. We believe that the large-scale production of PSB Gel-based therapeutic dressings has the advantages of easy use and promising clinical applications. Statement of significance: Rapid wound healing and the treatment of bacterial infections have always been the two biggest challenges in the field of wound care. We prepared a "live drug" dressing by encapsulating photosynthetic bacteria into an extracellular matrix hydrogel to sterilize the wound and promote wound healing. First, photosynthetic bacteria are not only a photothermal agent for photothermal wound sterilization, but also possess the anti-inflammatory capacity to enhance wound healing due to their antioxidant metabolites. Second, the extracellular matrix hydrogel is rich in a variety of growth factors and nutrients to promote cell migration and accelerate wound healing. Third, photosynthetic bacteria are not only green and non-toxic, but also can be obtained on a large scale, which facilitates manufacturing and clinical transformation. Graphical abstract: Image, graphical abstract